EXTENDED SPECTRUM Β- LACTAMASE PRODUCING SHIGELLA FLEXNERIA CASE REPORT: ESBL Producing Shigella Flexneri - Gilani, Mehreen; MunirMunir, Tehmina; Latif, Mahwish; Haroon, Amira; Rehman, Sabahat (Pakistan Armed Forces Medical Journal, 2016)
Infection by Shigella species is one of the major cause of morbidity especially in children with diarrhea. Extended spectrum β lactamases (ESBL) confer resistance to most of the beta-lactam antibiotics, including penicillins, cephalosporins and aztreonam. Its production in Shigellae is of concern especially in children, in whom treatment options are already limited. Third generation cephalosporins are used for treating diarrhea due to multidrug resistant Shigella species in children, but ESBL production renders them ineffective too. We report an extended spectrum β lactamase producing Shigella flexneri, isolated from the stool sample of a 3-year-old boy.